PELATIHAN PENINGKATAN KAPASITAS PEMUDA DAN PEMBUATAN PROGRAM KERJA PADA ORGANISASI PEMUDA DESA CIBINUANG, KABUPATEN KUNINGAN - Nursyamsu, Roni (Empowerment : Jurnal Pengabdian Masyarakat, 2018)
The Community Service Activity / Kegiatan pengabdian kepada Masyarakat (PKM) was held in Cibinuang Village, Kuningan District, Kuningan Regency with the target of young people who are members of Karang Taruna Tunas Mekar as youth organization in Cibinuang Village. The problems faced by partner institution in this activity are: a) lack of socialization about the existence of youth organizations and their roles in the development of rural communities, b) less awareness and participation of youth in organizations, both administrator/ other members, c) training of administrators / members in making work programs have never been done. The method of implementation in this activity is active participation with stages namely 1). Seminar and discussing about the role of youth organizations, 2). Providing technical training in making organization programs, 3) Mentoring in making proposals. Seminar about the roles of youth organization for community empowerment in youth organizations in Cibinuang Village presented material in accordance with the theme. The materials presented to the participants including: the role of youth in village development, the mechanism for preparing programs and how to make proposals for effective funding requests. The training in making organization programs and activity proposals were divided into three stages, namely lectures and discussion about the role of youth organizations, providing technical training in the preparation of organization programs and making activity proposals, and mentoring in making organization programs and proposals.  Based on the process PkM activities, it can be seen that 1) there were enhancing youth's understanding and awareness of their capacity in developing villages through youth organizations, 2) members and administrators of youth organizations were motivated to play an active / participating role in building themselves and their villages, 3) administrators of youth organizations to arrange a program, 4) the management of the youth organization was able to make a proposal from each organization program that will be submitted to the Cibinuang Village Government. Keywords: Youth Capacity, Youth Organization, Organization Program AbstrakKegiatan Pengabdian Kepada Masyarakat (PKM) ini dilaksanakan di Desa Cibinuang Kecamatan Kuningan Kabupaten Kuningan dengan target pemuda-pemudi yang tergabung dalam Karang Taruna Tunas Mekar yang merupakan organisasi kepemudaan di tingkat Desa Cibinuang.  Permasalahan yang dihadapi oleh lembaga mitra dalam kegiatan ini yaitu: a) kurang tersosialisasikanya eksistensi organisasi pemuda dan perannya dalam pembangunan masyarakat desa, b) kesadaran dan partisipasi pemuda dalam organisasi baik pengurus/anggota kurang, c) pelatihan pada pengurus/anggota dalam membuat program kerja belum pernah dilakukan.  Metode pelaksanaan dalam kegiatan ini yaitu partisipasi aktif dengan tahapan yakni 1). Ceramah dan tanya jawab tentang peran organisasi pemuda, 2). Memberikan pelatihan teknis pembuatan program kerja, 3) Pendampingan dalam membuat proposal kegiatan. Seminar tentang peran organisasi pemuda untuk pemberdayaan masyarakat pada organisasi pemuda di Desa Cibinuang Kec. / Kab. Kuningan diisi dengan pemaparan materi yang sesuai dengan tema. Materi-materi yang disampaikan kepada peserta meliputi: peran pemuda dalam pembangunan desa, mekanisme penyusunan program kerja dan cara pembuatan proposal kegiatan untuk permintaan dana yang efektif. Pelatihan pembuatan program kerja dan proposal kegiatan dibagi menjadi tiga kegiatan, yaitu ceramah dan tanya jawab tentang peran organisasi pemuda, memberikan pelatihan teknis penyusunan program kerja dan pembuatan proposal kegiatan, dan pendampingan dalam membuat program kerja dan proposal kegiatan. Berdasarkan proses kegiatan Pengabdian Kepada Masyarakat dapat dilihat adanya 1) peningkatkan pemahaman dan kesadaran pemuda terhadap kapasitasnya dalam membangun desa melalui wadah organisasi pemuda, 2) anggota maupun pengurus organisasi kepemudaan termotivasi  untuk berperan aktif/berpartisipasi dalam membangun diri maupun desanya, 3) pengurus organisasi kepemudaan dapat menyusun program kerja, 4) pengurus organisasi kepemudaan mampu membuat proposal kegiatan dari setiap program kerja yang akan diajukan ke Pemerintah Desa Cibinuang.